2023
DOI: 10.56397/ist.2023.01.04
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Nanomaterials: Types, Synthesis, Characterization Techniques, Properties and Applications

Abstract: Nanotechnology is science, technology, and engineering that is directed at the nano scale (1-100 nm). This is a diverse and attractive field, owing to its unique properties and applications. The surface- to- volume ratio is the most important property of a material, which makes a clear difference between bulk materials and materials at nano scale. Nano can be referring to materials, particles, thin films, wires, fibers, etc. Nanotechnology is a revolutionary method for developing of new systems and technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Their advancement relies on the production of semiconductor nanostructure materials of different kinds of metal oxides, along with their unique morphologies at nano scales. Compared to their bulk substances, semiconductor nanostructure materials of different metal oxides have highly impressive physio-chemical properties, such as electrical, optical, mechanical, and magnetic properties, besides catalytic and thermal stability, and can be used for various purposes [10,11]. Similarly, advanced research on semiconductor nanostructure materials has also shown that doped semiconductor nanostructure metal oxides have gained popularity in the field of nanoscience as they have impressive and excellent enhanced physio-chemical properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Their advancement relies on the production of semiconductor nanostructure materials of different kinds of metal oxides, along with their unique morphologies at nano scales. Compared to their bulk substances, semiconductor nanostructure materials of different metal oxides have highly impressive physio-chemical properties, such as electrical, optical, mechanical, and magnetic properties, besides catalytic and thermal stability, and can be used for various purposes [10,11]. Similarly, advanced research on semiconductor nanostructure materials has also shown that doped semiconductor nanostructure metal oxides have gained popularity in the field of nanoscience as they have impressive and excellent enhanced physio-chemical properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%